The Influence of Intermarriage (Java-Lampung) on Social Change in the Community in Gunung Sugih Village - Suma, Selviana; Setiawati, Elis; Setiawan, Johan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The aim of the research is to analyze Javanese and Lampung traditional marriages in Gunung Sugih Village, the factors that cause intermarriage, the implementationprocess, and the social changes that arise in society. The method used in this researchis qualitative research with a descriptive analysis approach. The subjects used in thisresearch were traditional leaders from the Lampung tribe, husband and wife couplesinvolved in intermarriage (amalgamation), Javanese people. Data collectiontechniques in this research used observation, interviews and documentation.Meanwhile, data analysis techniques are carried out by reducing, presenting data anddrawing conclusions. Based on the results of this research, it can be concluded that (1)Javanese and Lampung traditional marriages in Gunung Sugih Village, Gunung SugihDistrict, Central Lampung Regency, still maintain their respective traditions eventhough there are stages of Javanese customs that are not used. (2) The factors thatcause intermarriage to occur are feelings of love and a sense of compatibility,education, local environment and work. (3) The process includes pre-wedding,implementation and post-wedding stages, which combine the traditions of both tribes.(4) The social changes that occur include changes in social structure and kinshipintegration, changes in language and communication and marriage customs.